From a Soviet Paternalistic to the Market Model in Personal Social Services in Lithuania - Žalimienė, Laimutė (Socialinė teorija, empirija, politika ir praktika, 2020)
This article analyzes the development of personal social services (PSS) after the restoration of the independent state of Lithuania in 1990, looking through the lens of organizational peculiarities. The development of services in Lithuania occurred not only by introducing the principles of the welfare state but was also influenced by the marketization trends in the area, passing through the experience of the Western countries. Therefore, in Lithuania, the origination of PSS as a separate welfare sector and its marketization occurred almost in parallel.